STUDI PERBANDINGAN OBYEK WAKAF MENURUT FIKIH DAN UNDANG-UNDANG WAKAF - Sudirman, Sudirman (Fakultas Syariah, 2009)
WaqfÂ (endowment) is one of the charity-promoting activities, which promises Muslim the continuous rewards from the Almighty God although the doer (waqif) has passed away. Historically, the existence of waqfÂ has become a triggering factor for the development of Islamic proselytizing process all over the world, including Indonesia. In terms of the waqf objects, there are a lot of things that can be endowed. However, the objects can be viewed from two different angles: Islamic law (fiqh) and positive law (act). This piece of writing will elaborate both angles in detail so that the similar as well as the different aspects of both will be objectively observed.Wakaf merupakan salah satu aktifitas yang mendorong kegiatan karitas seorang Muslim. Wakaf juga menjanjikan pahala kekal abadi bagi pelakunya meskipun sang wakif sudah wafat. Dalam sejarah terlihat jelas bahwa keberadaan wakaf telah menjadi salah satu faktor penting yang mendorong proses dakwah Islam ke seluruh dunia, termasuk Indonesia. Dalam hal obyek wakaf, banyak benda-benda yang dapat diwakafkan. Obyek wakaf bisa dilihat dari dua sisi, yakni sisi fikih dan sisi hukum positif. Tulisan iniÂ akan memaparkan kedua perspektif itu sehingga persamaan dan perbedaan keduanya dapat dilihat secara objektif.